HLA class I variation in Iranian Lur and Kurd populations: high haplotype and allotype diversity with an abundance of KIR ligands. (24th August 2016) - Ashouri, E.; Norman, P. J.; Guethlein, L. A.; Han, A. S.; Nemat‐Gorgani, N.; Norberg, S. J.; Ghaderi, A.; Parham, P.
Abstract: HLA‐A, ‐B and ‐C alleles of 285 individuals, representing three Iranian Lur populations and one Iranian Kurd population were sequenced completely, yielding human leukocyte antigen (HLA) class I genotypes at high resolution and filling four fields of the official HLA nomenclature. Each population has 87–99 alleles, evenly distributed between the three HLA class I genes, 145 alleles being identified in total. These alleles were already known, named and deposited in the HLA database. The alleles form 316 different HLA A‐B‐C haplotypes, with each population having between 80 and 112 haplotypes. The four Iranian populations form a related group that is distinguished from other populations, including other Iranians. All four KIR ligands – the A3/11, Bw4, C1 and C2 epitopes – are well represented, particularly Bw4, which is carried by three high‐frequency allotypes: HLA‐A*24:02, HLA‐A*32:01 and HLA‐B*51:01 . In the Lur and Kurd populations, between 82% and 94% of individuals have the Bw4 epitope, the ligand for KIR3DL1. HLA‐B*51:01 is likely of Neandertal origin and associated with Behcet's disease, also known as the Silk Road disease. The Lordegan Lur have the highest frequency of HLA‐B*51:01 in the world. This allele is present on 46 Lur and Kurd haplotypes. Present at lower frequency is HLA‐B*51:08, which is also associated with Behcet's disease. In the four Iranian populations, 31 haplotypes encode both Bw4 + HLA‐A and Bw4 + HLA‐B, a dual combination of Bw4 epitopes that is relatively rare in other populations, worldwide. This study both demonstrates and emphasizes the value of studying HLA class I polymorphism at highest resolution in anthropologically well‐defined populations.